2004
DOI: 10.1002/pssb.200302000
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation of KH2PO4 above room temperature

Abstract: The dispersion curves of the dielectric response of KH 2 PO 4 were obtained from 5 Hz to 13 MHz and over the temperature range 120 -206 °C for both single crystal and polycrystalline samples. Both types of samples reveal dielectric relaxation at low frequency, for example around 10 4 Hz at 140 °C, which shifts to higher frequencies (~1 MHz) as the temperature increases. The relaxation frequency was determined from the peak obtained in the imaginary part of the permittivity as well as from the derivative of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 14 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…They argue that regular NH 4 + ions do not have a permanent strong dipole moment, but distortion can induce a dipole and thus, this relaxation can correspond to a reorientation or local jump. Our research team [16][17][18][19] observed that the dielectric response of MH 2 PO 4 (M = K + , NH 4 + ) and L 2 SO 4 (L = K + , Cs + ), reveals a dielectric relaxation at low frequency, for example for K 2 SO 4 around 1.4 × 10 4 Hz at 403 K, which shifts to higher frequencies (~10 6 Hz) as the temperature increases. We have suggested that this dielectric relaxation could be due to the proton jump and phosphate or sulphate reorientation that causes distortion and changes the local lattice polarizability inducing dipoles like H 2 PO 4 − in MH 2 PO 4 (M = K + , NH 4 + ) and like LSO 4 − in L 2 SO 4 (L = K + , Cs + , respectively).…”
Section: Introductionmentioning
confidence: 97%
“…They argue that regular NH 4 + ions do not have a permanent strong dipole moment, but distortion can induce a dipole and thus, this relaxation can correspond to a reorientation or local jump. Our research team [16][17][18][19] observed that the dielectric response of MH 2 PO 4 (M = K + , NH 4 + ) and L 2 SO 4 (L = K + , Cs + ), reveals a dielectric relaxation at low frequency, for example for K 2 SO 4 around 1.4 × 10 4 Hz at 403 K, which shifts to higher frequencies (~10 6 Hz) as the temperature increases. We have suggested that this dielectric relaxation could be due to the proton jump and phosphate or sulphate reorientation that causes distortion and changes the local lattice polarizability inducing dipoles like H 2 PO 4 − in MH 2 PO 4 (M = K + , NH 4 + ) and like LSO 4 − in L 2 SO 4 (L = K + , Cs + , respectively).…”
Section: Introductionmentioning
confidence: 97%
“…[2][3][4][5][6][7][8][9] The room temperature phase ͑phase II͒ is known to be paraelectric and ferroelastic while the low-temperature phase ͑phase III͒ is believed to be antiferroelectric. [14][15][16][17] The disorder of the oxygen and hydrogen atoms reflects thermal vibrations and reorientation of the H 2 PO 4 groups. TDP has a monoclinic crystal structure in phases II to III, and an orthorhombic structure in phase I.…”
mentioning
confidence: 99%
“…They argue that regular 4 NH + ions do not have a permanent strong dipole moment, but distortion can induce a dipole and thus, this relaxation can correspond to a reorientation or local jump. Furthermore, our research team [10][11][12] 4 . If the complex permittivity representation of measured dielectric data is used a relaxation is detected as a step in the real part and a peak in the imaginary part of the permittivity.…”
Section: Nhmentioning
confidence: 99%